Cardiac Surgery During the Coronavirus Disease 2019 Pandemic: Perioperative Considerations and Triage Recommendations. Issue 13 (7th July 2020) - Patel, Vivek; Jimenez, Ernesto; Cornwell, Lorraine; Tran, Trung; Paniagua, David; Denktas, Ali E.; Chou, Andrew; Hankins, Samuel J.; Bozkurt, Biykem; Rosengart, Todd K.; Jneid, Hani
Abstract: The coronavirus disease 2019 pandemic, caused by severe acute respiratory syndrome coronavirus‐2, represents the third human affliction attributed to the highly pathogenic coronavirus in the current century. Because of its highly contagious nature and unprecedented global spread, its aggressive clinical presentation, and the lack of effective treatment, severe acute respiratory syndrome coronavirus‐2 infection is causing the loss of thousands of lives and imparting unparalleled strain on healthcare systems around the world. In the current report, we discuss perioperative considerations for patients undergoing cardiac surgery and provide clinicians with recommendations to effectively triage and plan these procedures during the coronavirus disease 2019 outbreak. This will help reduce the risk of exposure to patients and healthcare workers and allocate resources appropriately to those in greatest need. We include an algorithm for preoperative testing for coronavirus disease 2019, personal protective equipment recommendations, and a classification system to categorize and prioritize common cardiac surgery procedures.